The Features of Leasing Activity Development: Russian Experience - VLADIMIROVNA, Zozulya Valentina; IVANOVNA, Goncharenko Lubov; VLADIMIROVICH, Zuykov Andrey; NIKOLAEVNA, Semenova Galina (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
Current political and economic situation in the world led Russian economy to the conditions when some actions to develop national production of goods, works and services have to be taken as an answer to international sanctions. Serious problems in the financial sector of the economy; dropping of oil prices, currency rate, budgetary deficit, in fact – the continuing process of recession, which can create more global problems – system crisis if emergency measures aren't made. One of the prospects to solve these tasks is the development of leasing relationships, what is actual and perspective. In this research the features of leasing relationships are considered and also their tax component; besides some measures of tax character to develop and restore the fields of economy, solve the problems of import substitution are mentioned in the research.